Enhanced Spin Accumulation in Semiconductor at Room Temperature Using Ni0.65Zn0.35Fe2O4(NZFO) as Spin Injector in NZFO/MgO/p-Si Device - Maji, Nilay; Shit, Subhasis; Nath, T. K. (Frontiers in Materials, 2021)
In this article, the fabrication of a Ni0.65Zn0.35Fe2O4/MgO/p-Si heterostructure device has been optimized using the pulsed laser deposition (PLD) technique, and a detailed investigation of its structural, electrical, and magnetic features has been performed experimentally. The electronic and magneto-transport characteristics have been explored in the temperature range of 100–300 K. The current-voltage (I-V) characteristics of the heterojunction have been recorded, which displayed an excellent rectifying magnetic tunnel diode-like behavior throughout that temperature regime. The application of an external magnetic field parallel to the plane of the NZFO film causes the current (I) across the junction to decrease, clearly indicating positive junction magnetoresistance (JMR) of the heterostructure. The root of displaying positive magnetoresistance in our heterojunction has been well justified using the standard spin injection model. The electrical injection of spin-polarized carriers and its accumulation and detection in a p-Si channel have been demonstrated using the NZFO/MgO tunnel contact using a three-terminal (3-T) Hanle device. The parameters such as spin lifetime (99 ps), spin diffusion length (276 nm), and spin polarization (0.44) have been estimated from the Hanle curve detected in our heterostructure at room temperature, making the Ni0.65Zn0.35Fe2O4/MgO/p-Si device a very favorable promising junction structure in the field of spintronics for several device appliances in the future.